Analysis of distortion-induced fatigue crack at the web gap of i-beam in steel bridges - Hung The Dinh (Chulalongkorn University, 2012)
Distortion-induced fatigue cracking has occurred in many types of steel bridge structures, especially the welded structures where high local stresses exist. However, out-of-plane distortion-induced stresses have not been fully considered in the AASHTO design specifications. This research studies the behavior around web-gap of I-beam in steel bridges under cyclic loading and applies the linear elastic fracture mechanics concepts for prediction of fatigue cracking behavior. Besides, effects of various parameters on the distortion-induced fatigue cracking behavior are considered experimentally and numerically. The results show that finite element modeling with SED criterion is applicable for the crack path prediction. In addition, mode I and mode III affected the fatigue crack direction and fatigue crack growth rate.